Methodological features of the project management system in the Government of the Republic of Kazakhstan - Oynarov, A.R.; Dushabaev, D.Sh.; Kartov, A.E. (BUKETOV BUSINESS REVIEW, 2017)
In Kazakhstan, project management tools have found application among large companies and banks in the quasi-public and private sectors of the economy, while in the public administration system they are still inadequate. To date, several government projects are being adopted in the Republic of Kazakhstan, such as, however, the effectiveness and effectiveness of projects implemented is not visible, as there are projects themselves, but there is no system for managing these projects. Today, project management’s system is actively implemented by the Government of the Republic of Kazakhstan. In this article it were considered and analyzed the methodological aspects of the project activity of the Government of the Republic of Kazakhstan, its problems, and also the ways of its solution. The authors reviewed the current legislative framework, where were identified problems in public administration. Then using information modeling approach and on the basis of the analysis, it was formed a current model of project management elements that does not cover all elements of the methodology of project management of the best world practices. The authors offer methodological tools for creating a system for managing the project activity of the Government of the Republic of Kazakhstan. Based on the analysis, it was also found that methodological tools need to be finalized in legislations, namely the institution of responsible secretaries, the methodology for evaluating the performance of civil servants of Corps "B", the system for assessing the activities of central government bodies, the system of motivation, regulations, groups of project management processes, which in turn should be linked to the national standard of the Republic of Kazakhstan: a project management manual.